Blood fibrinogen levels discriminate low- and high-risk intraductal papillary mucinous neoplasms (IPMNs). Issue 4 (April 2017) - Nentwich, M.F.; Menzel, K.; Reeh, M.; Uzunoglu, F.G.; Ghadban, T.; Bachmann, K.; Schrader, J.; Bockhorn, M.; Izbicki, J.R.; Perez, D.
Abstract: Backround: The risk assessment of intraductal papillary mucinous neoplasms (IPMN) to either guide patients to surgical resection or watchful waiting is still under debate. Additional markers to better separate low and high-risk lesions would improve patient selection. Methods: Patients who underwent pancreatic resections for IPMNs between January 2008 and December 2012 with available blood samples were selected and retrospectively assessed. Data on cyst characteristics such as cyst size, duct relation and main-duct dilatation were collected and plasma fibrinogen levels were measured. Results: A total of 73 patients fulfilled the inclusion criteria by pancreatic resection for pathologically confirmed IPMN and available blood sample. Histologically, IPMNs were classified as low-grade and borderline in 52 (71.2%, group 1) and as high-grade and invasive in 21 (28.8%, group 2) of all cases. Fibrinogen levels showed significant differences between the two groups (group 1: mean 3.62 g/L (SD ± 1.14); group 2: mean 4.49 g/L (SD ± 1.57); p = 0.027). A ROC-curve analysis calculated cut-off value of 4.71 g/L separated groups 1 and 2 (p = 0.008). Fibrinogen levels remained as the only significant factor in multivariable analysis, cyst size and duct relation were not significant. Conclusion: Blood fibrinogen differed between low and high risk IPMNs and therefore, the use of fibrinogen as an additional discriminator in the pre-operative risk assessment of IPMNs should be further evaluated.